ISU-ISU KRITIS DAN PERMASALAHAN PENDIDIKAN - Sukari; Nabila; Qonita Setyaningsih (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Advances in information and communication technology have transformed the way we learn and access information. Lack of technology integration in education or the inability to teach students to use existing technology can be problematic. Irrelevant Curriculum: An educational curriculum that is out of sync with the needs of the times or current economic and social needs can produce graduates who lack the skills needed by the workforce. This includes curricula that are overly theoretical and impractical. Teacher and Training Crisis: The quality of teaching depends heavily on the quality of teachers. Issues related to teacher training, updating teacher knowledge, and their ability to teach various subjects are at the heart of this crisis. Student Stress and Well-Being: Student well-being can impact their ability to learn. Excessive academic workload, mental stress, or other issues that affect student well-being can undermine the quality of education.